Use of unmalted cereals with enzyme preparations in brewing - Loiko, Serhii; Romanova, Zoriana; Zheplinska, Mariia; Romanov, Mykola; Vasyliv, Volodymyr (My University, 2024)
Using unmalted grain is one of the ways to improve quality, reduce production costs, and create new types of beer. However, the enzymatic activity of such raw materials is zero, so the use of enzyme preparations is relevant. The purpose of the study was to compare the quality indicators of 100% malt beer and beer with the replacement of malt with unmalted barley using enzymes. The methods of technical and chemical analysis were used to determine the organoleptic and physicochemical indicators of beer. Recommendations have been developed for the intensification of wort preparation using different types of grain raw materials - unmalted barley and rice groats with the addition of enzyme preparations from Novozymes (Denmark) at various stages of brewing. When testing new enzyme preparations (β-glucanase complex, xylanase), filtration time, wort viscosity and β-glucan content. and arabinoxylans decreased by approximately 20% compared to control samples. The use of a new enzyme preparation contributed to a better breakdown of substances, which affected the quality and duration of filtration. This leads to an improvement in the quality of the wort, a reduction in the duration of the process, and a reduction in the cost of raw materials. To ensure the necessary ratio of substances in the wort, it is necessary to introduce complex enzyme preparations - peptide hydrolase, α-amylase, endo-β-glucanase (Ceremis Plus). Preparations containing endo-β-glucanase (Ultraflo Max) should be used at the beginning of mashing to improve the rheological properties of the wort and reduce its viscosity, which improves the filtration process. To obtain beer with the required degree of fermentation during mashing, it is better to use new enzyme preparations (glucoamylase). The practical significance of the research is that the use of large amounts of unmalted grain together with exoenzymes such as Ultraflo Max and Ceremis Plus will allow brewers to produce worts and beers of the same composition and quality as premium worts and beers using only malt.

Використання несоложеного зерна є одним із способів підвищення якості, зниження витрати на виробництво, створення нових сортів пива. Проте ферментативна активність такої сировини матеріалів дорівнює нулю, тому актуальним є використання ферментних препаратів. Метою дослідження було порівняти показники якості 100% солодового пива та пива із заміною солоду на несолоджений ячмінь з використанням ферментів. Використовувалися методи технічного та хімічного аналізу визначати органолептичні та фізико-хімічні показники пива. Рекомендації є розроблений для інтенсифікації приготування сусла з використанням різних видів зернової сировини – крупа ячмінна та рисова несоложена з додаванням ферментних препаратів від Novozymes (Данія) на різних етапах пивоваріння були розроблені. При випробуванні нових ферментних препаратів (β-глюканазний комплекс, ксиланаза), час фільтрації, в’язкість сусла та вміст β-глюканів. і арабіноксиланів знизився приблизно на 20% порівняно з контрольними зразками. Використання нового ферментного препарату сприяв кращому розщепленню речовин, що вплинуло на якість і тривалість фільтрації. Це призводить до поліпшення якості сусла, скорочення тривалості процесу та зниження вартості сировини. Для забезпечення необхідного співвідношення речовин в сусла, необхідно ввести комплексні ферментні препарати – пептидгідролазу, α-амілазу, ендо-β-глюканаза (Ceremis Plus). Препарати, що містять ендо-β-глюканазу (Ультрафло Макс) слід використовувати на початку затирання для покращення реологічних властивостей сусла та зменшують його в'язкість, що покращує процес фільтрації. Для отримання пива з необхідним градусом бродіння при затиранні краще використовувати нові ферментні препарати (глюкоамілаза). Практичне значення дослідження полягає у використанні великої кількості несоложеного зерна разом з екзоферменти, такі як Ultraflo Max і Ceremis Plus, які дозволять пивоварам виробляти сусло та пиво такого ж складу та якості, що й сусло та пиво преміум-класу, з використанням лише солоду.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка; barley; beer; wort; malt; barley; ber; shorts; malt